Structural Engineering Effects on Hump Characteristics of ZnO/InSnO Heterojunction Thin-Film Transistors - Qi Li; Junchen Dong; Dedong Han; Dengqin Xu; Jingyi Wang; Yi Wang (Nanomaterials, 2022)
Transparent conductive oxides (TCO) have been extensively investigated as channel materials for thin-film transistors (TFTs). In this study, highly transparent and conductive InSnO (ITO) and ZnO films were deposited, and their material properties were studied in detail. Meanwhile, we fabricated ZnO/ITO heterojunction TFTs, and explored the effects of channel structures on the hump characteristics of ZnO/ITO TFTs. We found that Vhump–VON was negatively correlated with the thickness of the bottom ZnO layer (10, 20, 30, and 40 nm), while it was positively correlated with the thickness of the top ITO layer (3, 5, 7, and 9 nm), where Vhump is the gate voltage corresponding to the occurrence of the hump and VON is the turn-on voltage. The results demonstrated that carrier transport forms dual current paths through both the ZnO and ITO layers, synthetically determining the hump characteristics of the ZnO/ITO TFTs. Notably, the hump was effectively eliminated by reducing the ITO thickness to no more than 5 nm. Furthermore, the hump characteristics of the ZnO/ITO TFTs under positive gate-bias stress (PBS) were examined. This work broadens the practical application of TCO and provides a promising method for solving the hump phenomenon of oxide TFTs.